Role of cycle threshold values in predicting poor outcomes in patients with Kyasanur Forest disease: a retrospective cohort study - Nitin Gupta; Praveen Kumar Tirlangi; Sudheesh N; Pothumarthy Venkata Swathi Kiran; Muralidhar Varma; Chiranjay Mukhopadhyay (Annals of Medicine)
Background Kyasanur Forest Disease (KFD) is a tick-borne viral haemorrhagic illness endemic to southern India. Early identification of patients at risk for poor outcomes remains a clinical challenge. The study aimed to evaluate the role of cycle threshold (Ct) values in predicting outcomes.Methods We conducted a retrospective cohort study of adults with PCR-confirmed KFD admitted to a tertiary care hospital in South India between January 2019 and December 2024. The primary outcome was 28-day all-cause mortality. Univariate and multivariable logistic regression analyses were performed to identify independent predictors of mortality. Receiver operating characteristic (ROC) analysis was used to assess the prognostic performance of Ct values.Results Among 213 patients, 20 (9.4%) died. Mortality was independently associated with lower Ct values, older age, lower respiratory tract involvement, altered sensorium, and elevated white blood cell counts on multivariable analysis. ROC analysis yielded an area under the curve of 0.675 for Ct value alone. A Ct cut-off ≥27.75 predicted survival with 68.4% sensitivity and 70.0% specificity.Conclusion Lower Ct values are independently associated with increased mortality in KFD and may serve as a pragmatic tool for early risk stratification, especially in resource-limited settings.